Long-Term Seizures Outcome in Juvenile Myoclonic Epilepsy (JME): A Retrospective Cohort Study in an Indian Population - Viswanathan, Lakshminarayanapuram Gopal; Mundlamuri, Ravindranadh Chowdary; Raghavendra, Kenchaiah; Asranna, Ajay; Chatterjee, Aparajita; Gautham, Bhargava; Satishchandra, Parthasarathy; Sinha, Sanjib (International Journal of Epilepsy, 2021)
Objectives Juvenile myoclonic epilepsy (JME) is the most prevalent form of generalized epilepsy in the community. Though the response to medication is good in most patients, long-term medication usage may lead to poor compliance, side effects, and other epilepsy-related social issues. The aim of this study was to describe the demography, clinical features, and therapeutic response in patients with JME who have had at least 10 years of duration of epilepsy.Materials and Methods A retrospective study of 56 patients (M:F=26:30; mean age: 14.5 ± 5.1 years) with JME attending neurological services in a tertiary care neurological center in South India with more than 10 years disease duration was performed.Results All patients had myoclonic jerks, 94% had generalized tonic–clonic seizure, and only 7.1% had features of absence seizures. Seizures were controlled in 60% of cases at the end of 10 years of epilepsy. Thirty-eight patients (67.8%) were on valproate. Control of seizures at the end of the first and fifth years of epilepsy, frequent myoclonic jerks at the onset, and treatment with valproate in the first year of disease resulted in controlled seizures at the end of 10 years. No patient was off medications at the end of 10 years of epilepsy or at the last follow-up.Conclusion About 40% of our patients continued to have seizures even 10 years after the onset of epilepsy. Regular and long-term medication may be required in JME. Early control of seizures, response to valproate, and frequent myoclonia at onset were found to confer better prognosis.
Keywords: juvenile myoclonic epilepsy; prognostic factors in JME; sodium valproate